Alternative Dispute Resolution and State Legitimacy in Sudan: A Socio-Legal Analysis of Informal Justice and Governance Fragmentation - Fatima Abdelnasir Hammad Ahmed (Priviet Social Sciences Journal, 2026)
State legitimacy in fragile political environments is increasingly shaped by the interaction between formal legal institutions and informal systems of dispute resolution, yet existing scholarship often treats alternative dispute resolution (ADR) either as a technical access-to-justice mechanism or as a culturally bounded expression of legal pluralism. This framing insufficiently explains how informal justice systems participate in the redistribution of governance authority under conditions of institutional fragmentation. This article examines how ADR mechanisms in Sudan function as politically embedded structures of legitimacy production within a fragmented governance order characterized by conflict, contested sovereignty, and weakened state institutions. Drawing upon a qualitative socio-legal and interpretive governance research design grounded in legal pluralism and postcolonial institutional analysis, the study analyzes constitutional frameworks, institutional reports, governance materials, and socio-legal scholarship relating to Sudan’s informal justice landscape between 2005 and 2025. The findings demonstrate that ADR mechanisms operate not merely as supplementary legal forums, but as parallel governance infrastructures that simultaneously stabilize localized order and deepen fragmented sovereignty. The article advances scholarship by reconceptualizing informal dispute resolution as a legitimacy-producing governance structure rather than a peripheral procedural alternative, thereby refining prevailing understandings of legal pluralism, fragile statehood, and institutional authority in conflict-affected societies.